A novel ring-shaped vibration damper based on piezoelectric shunt damping: Theoretical analysis and experiments. (3rd March 2020) - He, Huan; Tan, Xing; He, Jincheng; Zhang, Fang; Chen, Guoping
Abstract: In this paper, a novel ring-shaped piezoelectric damper is proposed; meanwhile, vibration control on a single-DOF system is performed by using it. This damper, called vibration ring, may be used for vibration control of rotating machinery. It has the appearance of a metal ring and can be installed between supporting structure and bearing house. Damping is achieved using piezoelectric stack connected with series resonant RL shunts as fundamental element. Surrounding the stack is a metal structure, which squeezes the stack along its poled axis when the damper is excited by radial forces. Due to its unique configuration, this damper is stiffer than traditional damping devices and can protect stacks very well. In order to analyze and demonstrate the performance of such damper, the electromechanical coupling equation of this damper is firstly derived. Next, the force transmissibility between simplified rotor/shaft and supporting structure is obtained from the foregoing equation in Laplace form. Then the optimum inductance value of shunt circuit is determined. Finally, the performance of vibration ring is demonstrated through simulations and experiment based on a test rig. The experimental results show that the force transmissibility is reduced about 57.75% at resonant frequency.